Dependence of psychological maturity on the strength of family relationships. (Eurasian Journal of Humanities and Social Sciences, 2022)
The family plays a significant role both in the formation of a person and in his further independent life. In recent years, quite a lot of work has been published in which various family crises, destructive changes - conflicts, violations of education, pathologies of family members, the problem of divorces are considered .